Editorial: Binge drinking: lessons from ATF3 and HDAC1 collaboration. Issue 3 (1st March 2017) - Saha, Banishree
Abstract : Discussion on the role of ATF3 in LPS tolerance during binge drinking, and its interaction with cofactor HDAC1.